Social care services for the homeless people based on the attitudes of residents towards homelessness - Lucia Ludvigh Cintulová (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
There is no Strategic Plan for tackling and preventing homelessness in Slovakia, which exacerbates the unsystematic process of social services for homeless people. For this reason, we point out the positives and negatives of the whole system. The research focuses on mapping the current situation of homelessness and describes the aid system under the auspices of the non-profit sector. The participants in the research were social and street workers who provide care and counseling for the homeless on an outpatient basis, on a residential basis or directly in the street where they live.